2018
DOI: 10.5731/pdajpst.2018.008771
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Quality Culture on Operational Performance—An Empirical Study from the Pharmaceutical Industry

Abstract: Quality culture as an enabler of high-quality performance and subsequently as a source of competitive advantage is increasingly discussed among operational excellence (OPEX) and quality executives. Research studies indicate an impact of quality culture on performance, especially on the success of quality improvement programs, such as Total Quality Management initiatives. A continual challenge in quality culture research, however, remains the lack of practical and accepted metrics to assess culture. In 2014, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…breaks in the chain will cause problems in implementing quality practices ). Friedli et al (2018) state that "Quality culture as an enabler of high-quality performance " (quality culture is a driving factor for the emergence of high-quality performance). Hilman & Abubakar (2017) state that "quality culture has a significant positive effect on university performance".…”
Section: The Influence Of Quality Culture On the Performance Of Publi...mentioning
confidence: 99%
“…breaks in the chain will cause problems in implementing quality practices ). Friedli et al (2018) state that "Quality culture as an enabler of high-quality performance " (quality culture is a driving factor for the emergence of high-quality performance). Hilman & Abubakar (2017) state that "quality culture has a significant positive effect on university performance".…”
Section: The Influence Of Quality Culture On the Performance Of Publi...mentioning
confidence: 99%
“…Using the independent t-test and the multiple linear regression, they found that more OPEX implementation leads to higher QC labs effectiveness, which is characterized by indicators of customer complaint investigation rate, invalidated OOS, delayed CAPAs, QC lab deviations, and their reoccurring deviations. They also studied the relationship between quality culture behavior and quality system maturity based on the survey data of 336 manufacturing sites in 2018 and found that higher-performing OPEX leads to more timely release of products, higher level of quality culture behavior, and quality system maturity [8]. They also found, based on a survey of 61 manufacturing sites from 2009 to 2019 and using t-test, a positive correlation between higher-performing OPEX and better FDA inspection outcome in terms of inspection classification, which includes no action indicated (NAI), voluntary action indicated (VAI), and official action indicated (OAI), with a significance level at 5% of t-test [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hilman, Abubakar y Kaliapan (2017); Friedli et al (2018); y, Andhika y Latief (2020), han señalado que la cultura de calidad ejerce una influencia significativa en el rendimiento de las organizaciones, generando mejoras tanto en la satisfacción del cliente como en la reducción de costos y el aumento de la eficiencia. En este sentido, es crucial la participación de todos los miembros de la organización, así como el liderazgo de la alta dirección, para fomentar el desarrollo de una cultura de calidad sólida.…”
unclassified